Nano-Selenium as a Key Supplement in Rabbit Nutrition: Physiological and Productive Benefits-A Review - Abd El-Aziz, A.; Noreldin, A.; Elbaz, A.; Mishra, B.; Buonaiuto, G.; El-Sabrout, K. (Faculty of Animal Science, IPB University, 2025)
Nutrition is a vital component of health, productivity, and performance. During the last decades, nanotechnology has been highlighted as an innovative technique in the area of animal nutrition, which is used for improving nutrient utilization/supply and maintaining the health of the animal. Among the nano-minerals, selenium nano-particles (Nano-Se) have been of exceptional interest because of higher bioavailability and biological activity than the traditional sources of Se. Nano-Se is essential for growth performance, gut health, and immunity in rabbits. The absorption of trace elements is essential for an animal’s growth and productivity. Nano-Se has exhibited visible potential in advancing physiological processes, functioning as an effective antioxidant and anti-inflammatory agent. These attributes result in better immune response, healthier guts, and proper organ function. Moreover, selenium is well known for its vital role in immune regulation, digestion, and metabolism. Several reports are available on the beneficial effects of Nano-Se supplementation on production performance, reproductive performance, carcass characteristics, and meat quality in rabbits. By modulating the expression of tight junction proteins, Nano-Se safeguards gut barrier function, improves hematobiochemical profiles, and supports tissue histology. Therefore, Nano-Se not only enhances biological performance but also the economic efficiency of rabbit production. The review provides a comprehensive and updated overview of the action mechanisms, effective dosage levels, and physiological effects of Nano-Se on rabbit growth, nutrient digestibility, reproduction, immunity, and intestinal health. It also stresses the necessity of precise selenium supplementation and indicates the range of optimum dietary selenium levels between 0.05 and 0.3 mg/kg, depending on the diet composition. Further research is needed to establish proper and safe Nano-Se supplementation guidelines for sustainable rabbit production.